Arsenite-induced downregulation of occludin in mouse lungs and BEAS-2B cells via the ROS/ERK/ELK1/MLCK and ROS/p38 MAPK signaling pathways. (10th October 2020) - Liu, Yingqi; Tang, Jing; Yuan, Jiaming; Yao, Chenjuan; Hosoi, Kazuo; Han, Yu; Yu, Shali; Wei, Haiyan; Chen, Gang
Highlights: As2 O3 decreased occludin expression in mouse lungs and BEAS-2B cells. As2 O3 decreased occludin partially via the ROS/ERK1/2/ELK1/MLCK signaling pathway. As2 O3 decreased occludin partially via the ROS/p38 MAPK signaling pathway. Abstract: Occludin is an important tight junction (TJ) protein in pulmonary epithelial cells. In this study, we identified changes in occludin in arsenic-induced lung injury in vivo and in vitro . Upon intratracheal instillation with arsenic trioxide (As2 O3 ) at a daily dose of 30 μg/kg for 1 week, levels of occludin mRNA and protein expression decreased significantly in mouse lung tissue. Levels of occludin mRNA and protein expression in BEAS-2B cells were reduced upon exposure to As2 O3 in a concentration- and time-dependent manner. In addition, exposure to As2 O3 significantly increased expression of p-p38, p-ERK1/2, p-ELK1, and MLCK in mouse lung tissue and BEAS-2B cells. Treatment with As2 O3 induced oxidative stress in mouse lung tissue and BEAS-2B cells. In BEAS-2B cells, exposure to As2 O3 reduced transepithelial resistance, which was partially restored with N-acetyl-cysteine (NAC) treatment. Reduced expression of occludin mRNA and protein induced by As2 O3 was entirely restored with NAC and resveratrol. However, SB203580, PD98059, and ML-7 partially blocked As2 O3 -induced occludin reduction in BEAS-2B cells. These results indicate that As2 O3 inhibits occludin expression in vivo and in vitro at least partially via the ROS/ERK/ELK1/MLCK and ROS/p38 MAPK signaling pathways.